2013
DOI: 10.1117/12.2007673
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticle hyperthermia: predictive model for temperature distribution

Abstract: Magnetic nanoparticle (mNP) hyperthermia is a promising adjuvant cancer therapy. mNP’s are delivered intravenously or directly into a tumor, and excited by applying an alternating magnetic field (AMF). The mNP’s are, in many cases, sequestered by cells and packed into endosomes. The proximity of the mNP’s has a strong influence on their ability to heat due to inter-particle magnetic interaction effects. This is an important point to take into account when modeling the mNP’s. Generally, more mNP heating can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The effects of magnetic dipolar interactions on the MNP hysteresis and heating efficiency have recently been studied intensively. [17][18][19][20][21][22][23][24][25][26][27]34,39,63 These studies have demonstrated a strong interaction effect between MNP aggregates and have attributed it to the observed MNP hysteresis. However, the detailed mechanism of the power loss in a MNPs assemblies, which exhibit particle-particle, particle-aggregate, and aggregate-aggregate strong and weak interactions, are not yet known.…”
Section: B Nanoparticle Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…The effects of magnetic dipolar interactions on the MNP hysteresis and heating efficiency have recently been studied intensively. [17][18][19][20][21][22][23][24][25][26][27]34,39,63 These studies have demonstrated a strong interaction effect between MNP aggregates and have attributed it to the observed MNP hysteresis. However, the detailed mechanism of the power loss in a MNPs assemblies, which exhibit particle-particle, particle-aggregate, and aggregate-aggregate strong and weak interactions, are not yet known.…”
Section: B Nanoparticle Characterizationmentioning
confidence: 91%
“…30,31 These induced eddy currents can result in significant heating of normal tissue and impose limitations on the product of magnetic field strength and frequency (HÁf) for hyperthermia treatment. [32][33][34] The HÁf limitations that clinical test subjects were able to withstand for more than 1 h without major complications have been reported in four independent studies; 32,35-37 the limit varies from 4:5 Â 10 8 A=ðm sÞ or ð5:625 Â 10 6 Oe=sÞ to 8:5 Â 10 8 A=ðm sÞ or ð10:625 Â 10 6 Oe=sÞ and is summarized in Ref. 38.…”
mentioning
confidence: 93%
“…The software can then calculate the expected heat distribution within the brain at various magnetic field amplitudes [64]. One group has validated a coupled electromagnetic and thermal model to predict dynamic and thermal distributions during AMF treatment [65]. Variables such as tissue density, specific heat of tissue, thermal conductivity of tissue, and metabolic heat generation rate were used in a variation of the BHTE equation.…”
Section: Magnetic Hyperthermia Therapymentioning
confidence: 99%
“…It is powered by a 25kW generator (Radyne Corp., Milwaukee, WI, USA), which drives 135–400kHz AC current through the coil, thus generating a 135–400kHz AMF [56]. The frequency used in the following experiments was 162kHz.…”
Section: Methodsmentioning
confidence: 99%